The Numbers Line Media to Improve the Ability of the Students In Calculating Integer Operation - Muhammad Sholahuddin Arif; Kholifah Kholifah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
The interested thing to study on the teaching and learning strategies in elementary school is the understanding of the development of the learners at once the uniqueness that is required the teachers on identifying suitable actions (behavior in children) as a goal that can be achieved in the teaching, the activities and the learning experiences for certain age groups, and the evaluation system to be used. Therefore, this reason become strong in order to the teaching system that was developed by the teacher is expected to be increasingly able to serve the requirements of the individual learner (individually guided education) and the teaching become interested and meaningful for children. Moreover, the purpose of this study is used to improve the learning outcomes of the mathematics subject which calculate the Additional Operation and Integer Reduction material, especially at remote rural schools. In addition, the purpose is to determine the extent of the effectiveness of the use of numbers board media to improve the mathematics achievement which calculates the Additional Operation and Integer Reduction material in class IV SDN Bektiharjo VI Kecamatan Semanding. The data that used were obtained from the test results and observations of the students in the process of the teaching and learning by the number of 24 children. The result of this study that was obtained by the observation from the teacher to the students on the learning process has increased in each cycle. In the first cycle of the observation has the total score is 52 and it has increased on the second cycle which has the total score is 69. Furthermore, the result of the students’ mathematic subject which the school standard value of SDN Genaharjo VI is 70 was also increased from the first cycle of the total value in 1650 with an average of 68.7 and the second cycle of the total value in 2030 with an average of 84.5.